Android-Based Elementary Linear Algebra Learning Media - Haikal Nadhar Bidawi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2022)
This research is driven by the importance of android-based learning media in Elementary Linear Algebra learning, namely facilitating student understanding in understanding the existing material, because students do not understand the learning conveyed by the lecturer and the time is short, this can reduce student interest and have difficulty in understand the material. This study uses the Research and Development method using the Luther Sutopo model. The product was tested using Aiken's "V" formula for validity testing, Moment kappa formula for practicality testing and Gain Score formula for effectiveness testing. Based on the three tests, it was found that the product was valid with a value of 0.79, practical with a value of 1 and effective with a value of 0.85. This product can make it easier for students to repeat the material that has been conveyed by the lecturer in class so that students can understand the material well.